Pendampingan Usaha Woow Bordir melalui Pelatihan Manajemen Keuangan dan Akuntansi di Cipatat Kabupaten Bandung Barat - Ika Sri Hastuti; Yanti Purwanti; Loren Christy Sebayang; Valencia Dilla Berlian (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2022)
After the COVID-19 pandemic which paralyzed many MSMEs so that they could not carry out business activities, many MSMEs were temporarily closed and even went bankrupt. One of the MSMEs in Bandung Regency, Woow Embroidery, is one of the MSMEs experiencing the impact of the COVID 19 pandemic. After the post-pandemic release of social restrictions, Woow Embroidery MSMEs have started to run their business again. The problem faced is that there are still many MSMEs that have not made financial records and business management in order to be able to calculate the cost of production, because the price of raw materials continues to rise. From the results of the analysis of the situation, the servant proposes to Woow Embroidery MSME partners to provide training and simple financial administration assistance that aims to provide knowledge to partners about financial management. The method used is to provide simple financial administration training, namely partners are given manual recording exercises in the cash book. Furthermore, assistance to partners to find out the implementation of financial administration training results manually and using Microsoft excel. In the implementation stage, partners are invited to take part in financial administration training with resource persons who master accounting and financial management. Partners are given theoretical and practical knowledge as well as the benefits of routine financial records to find out the company's financial condition and partners are directly given exercises by recording in the manual cash book that has been provided. After 2 (two) weeks of mentoring, namely visiting partners and checking the results of financial administration training and the obstacles faced by partners in recording manual financial administration and copying in the excel program. From the results of the training and mentoring activities, partners get financial knowledge as well as the condition of their business financial management. Keywords: Training, Mentoring, Financial Administration, MSME